Biochemical Diagnosis of Common Gene Mutations in Galactosemia - Farzaneh Mirzajani; Reza Mirfakhraei; Neda Naghib-Zadeh; Farah Nabati; Sasan Saki; Elham Talachian; Masoud Houshmand (Journal of Rehabilitation, 2005)
Objective: Galactosemia is an inborn error of galactose metabolism that is inherited in an autosomal recessive trait. Classical galactosemia is caused by deficient activity of the galactose-1-phosphate uridyltransferase (GALT) enzyme that can result in galactosemia complications.